Pembiasaan Tilawah Harian sebagai Strategi Peningkatan Kelancaran Membaca Al-Qur’an Siswa Madrasah Tsanawiyah - Tsaqifa Qoniatuz Zahro; Nasirudin Nasirudin; Bakti Fatwa Anbiya; Lilif Muallifatul Khorida Filasofa (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2026)
The development of religious character in madrasah students still faces challenges, particularly in consistently cultivating the habit of reading and interacting with the Qur'an. This study aims to analyze how implementing a Qur'an recitation habit program contributes to the development of students' religious character. This study uses a qualitative approach. Data collection techniques involved interviews and observations, while data analysis followed the stages of data reduction, data presentation, and drawing conclusions. The results showed that the recitation activity was carried out in a structured manner every morning before class: reading the Qur'an together, guided by the teacher, accompanied by tajwid guidance, and with student reading monitored. The implementation of this program contributed to increased fluency in reading the Qur'an, greater discipline in participating in religious activities, and the creation of a religious learning atmosphere. The role of teachers in guiding, directing, and motivating students is an important factor in maintaining the program's sustainability. Supporting factors for program implementation include teacher commitment, student participation, and the Qur'anic culture that develops in madrasahs, while obstacles include differences in students' Qur'an-reading abilities and the need for ongoing supervision. The findings of this study indicate that the habit of reciting the Qur'an contributes to the development of students' religious habits and to the strengthening of Qur'anic culture, making it one of the strategies for strengthening religious character in Islamic education practices.